Graft copolymer electrolytes for high temperature Li-battery applications, using poly(methyl methacrylate) grafted poly(ethylene glycol)methyl ether methacrylate and lithium bis(trifluoromethanesulfonimide). (1st September 2015) - Bergman, Martin; Bergfelt, Andreas; Sun, Bing; Bowden, Tim; Brandell, Daniel; Johansson, Patrik
Abstract: For successful hybridization of heavy vehicles, high temperature batteries might be the solution. Here, high temperature solid polymer electrolytes (SPE's) based on different ratios of poly(methyl methacrylate) (PMMA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA), with LiTFSI salt (at a fixed ether oxygen (EO):Li ratio of 20:1) have been prepared and investigated. The copolymers comprise PMMA backbones with grafted PEGMA side-chains containing 9 EO units. The SPE systems were characterized using Raman spectroscopy, broadband dielectric spectroscopy, differential scanning calorimetry, thermal gravimetric analysis, and electrochemical cycling in prototype cells, with a particular focus on the 83 wt% PEGMA system. The electrolytes have good thermal stabilities and dissociate the LiTFSI salt easily, while at the same time maintaining low glass transition temperatures (Tg 's). Depending on the polymeric structure, ionic conductivities >1 mS cm −1 at 110 °C are detected, thus providing ion transport properties for a broad range of electrochemical applications. Prototype Li|polymer electrolyte|LiFePO4 cells utilizing the SPE at 60 °C showed surprisingly low capacities (<20 mA h g −1 LiFePO4 ), which could be due to poor electrode/electrolyte contacts.